Analyzing the Efficiency and Profitability Evidence from Chinese Commercial Banks after the 2008 financial crisis - Yao, Quanyi
After the 2008 financial crisis during the period of 2009 to 2014, the Chinese banking system has gone through further banking reform and policy development alongside efficiency and profitability enhancement. Thus, this study is aim to estimate the determinants of Chinese banking sector profitability by employing 32 Chinese commercial banks. It divides the determinants into bank specific variables (assets size, assets quality et.al), macroeconomic variables (GDPGR, inflation and concentration), which affect bank profitability, which is estimated by ROE. This paper conducts a two-stage estimation. The first stage is to estimate the X-efficiency for each commercial bank by using the stochastic frontier approach (SFA). The second stage is estimating the determinants of bank profitability by using the system GMM. Overall, the results report that different variables have different effects on Chinese commercial banks’ profitability.